From clinical competence to human connection: A reflective journey to patient‐centred care - David Gringras (Wiley, 2024)
Abstract Introduction This reflective essay explores a medical student's evolving understanding of the relative roles of technical and interpersonal skills in shaping the patient experience. Methods The author's personal reflections on the relative roles of technical and interpersonal skills are supplemented with discussion of relevant literature. Results and Discussion Initially focused on the technical aspects of medicine, the author's perspective shifts upon entering clinical practice. The essay begins by emphasising the importance of interpersonal skills in patient satisfaction, drawing on personal experiences from general practice and supporting literature. However, a pivotal experience on a respiratory ward reveals the profound impact of interpersonal skills on both patient satisfaction and clinical outcomes. With further reflection incorporating relevant literature, it becomes clear that this case in‐fact underscores the interplay between technical knowledge and interpersonal skills. Conclusion The reflective exploration concludes with the insight that these skillsets are not independent but interdependent and synergistic. The essay thus advocates for an integrated approach (combining technical expertise with strong interpersonal communication) to foster patient partnerships and enhance the overall patient experience.